Design and development of solar dryer for biomaterials processing - Al-Mardof, Ahmed Saeed, 1990- , author; Jamaliah Idris, supervisor 225354; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2016